Natural supramolecular photosensitizer with in situ switchable photothermal/photodynamic effects as an imaging platform for precise and controlled cancer synergistic therapy - Shiyao Fu; Jianjun Cheng; Hua Zhang; Haitian Zhao; Jiacheng Wang; Jing Wang; Xin Yang (Acta Materia Medica)
Treatment of cancer can be challenging, because of the disease’s intricate and varied nature. Consequently, developing nanomedicines with multimodal therapeutic capabilities for precise tumor therapy holds substantial promise in advancing cancer treatment. Herein, a nanoplatform strategy involving supramolecular photosensitizers (ETSCe6 NPs) and chelated metal ions (Au and Bi) was found to induce a shift in tumor microenvironment responsiveness from photothermal therapy to photodynamic therapy, thus facilitating tumor visualization for precise diagnosis and treatment. Self-assembly of supramolecular photosensitizers enhanced photothermal therapy through aggregation-caused quenching. Moreover, glutathione triggered disulfide bond cleavage, and consequently Ergosterol (ET) and Chlorin e6 release. Therefore, chemotherapy and photodynamic therapy achieved synergistic anticancer effects. Ce6 cavities were also used to chelate high valence Au and Bi metal ions for computed tomography. The ETSCe6@Au, Bi NPs demonstrated remarkable efficacy in vitro and in vivo , achieving complete tumor elimination after treatment. This integrated approach combining imaging, chemotherapy, photodynamic, and photothermal therapies has substantial promise for clinical applications, and may provide an innovative strategy for developing intelligent nanomedicines with promising prospects.